Antiquarians and Avocationals from Upper Canada to Ontario - Fox, William; Heidenreich, Conrad; Hunter, James (Ontario History, 2018)
The investigation of Indigenous and European archaeological sites in what is now the Province of Ontario spans a period of nearly two centuries. While much of the earliest work involved “digging for curiosities,” establishment of the Canadian Institute in 1849 resulted in a more scientific pursuit of knowledge. With the creation of a Provincial archaeologist and the staffing of academic positions, the professional and avocational/collector branches of archaeological activity split in the latter decades of the 19th century; however, both remained active. The interplay between them strengthened the still nascent professional branch during the early 20th century, leading to the increased professionalization of the discipline in the second half of the century.